Groundnut (Arachis hypogaea L.) and cowpea (Vigna unguiculata L. Walp) growing in Ethiopia are nodulated by diverse rhizobia - Degefu, Tulu; Woldemeskel, Endalkachew; Ataro, Zikie; Fikre, Asnake; Amede, Tilahun; Ojiewo, Christopher Ochieng (Academic Journals, 2018)
A total of eighty one (81) rhizobial isolates were recovered from root nodules of cowpea (Vigna unguiculata L. Walp.) and groundnut (Arachis hypogaea L.) grown in soils collected from eight different sites (Hawassa, Wondogenet, Chofa, Badawacho, Bodity, Gofa, Ziway, and Alemtena) in Ethiopia with no known history of inoculation. The test isolates together with seven reference strains belonging to five genera including Rhizobium, Ensifer, Mesorhizobium, Bradyrhizobium and Azorhizobium were characterized using ninety phenotypic traits. Thirty one isolates (38%) were found to be fast growers while fifty isolates (62%) were slow growers. The majority of the isolates showed an intrinsic resistance to antibiotics (µg/ml), Chloramphenicol (5 and 15), Lincomycin (100), Novobiocin (0.5 and 1.5), and Erythromycin (10 and 20) and to heavy metals manganese sulphate (500) and copper chloride (100). Most isolates did not tolerate NaCl concentration >3% (w/v) and high temperature (45°C). Dendrogram was constructed by applying the unweighted pair group method with arithmetic means (UPGMA) using NTSYSpc Version 2.1. They were grouped into seven clusters and eight unclustered positions, when 82% relative similarity was used as a cut point. Fifty eight percent of the test isolates were grouped with Bradyrhizobium japonicum and Bradyrhizobium elkanii superclades, thus indicating that rhizobia nodulating cowpea and groundnut are delineated within a branch that defines Bradyrhizobium genus. To elucidate the precise taxonomic positions of the isolates, further genetic studies are required using modern molecular biological methods.